2018
DOI: 10.2214/ajr.17.18994
|View full text |Cite
|
Sign up to set email alerts
|

A Women in Radiology Group Fosters Career Development for Faculty and Trainees

Abstract: A WIR group can provide career development tools for its members. In this study, trainees and junior faculty reported increased networking and research involvement and gaining a mentor but were equally likely as senior faculty to have become mentors. Most members reported increased camaraderie among women in the department. A WIR group may help to accelerate professional development among trainees and junior faculty, thereby contributing to a more diverse and enabled workforce.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…Other research on female physicians and female entrepreneurs suggests women's more limited engagement in networking may be due to a lack of aspiration for organization leadership, lack of time, or a focus on seeking advice from within a smaller social circle (Chae, 2018;Mariam Malende, 2017). Regardless of the specific reasons, promoting same-sex mentorship is important as female students and trainees traditionally lack academic and professional mentors (Association of American Medical Colleges, 2017; Butkus et al, 2018;Colón-Emeric, Bowlby, and Svetkey, 2012;Burk-Rafel, Santen, and Purkiss, 2017;DeFilippis et al, 2016;Faucett et al, 2017;Gaetke-Udager et al, 2018;Lautenberger et al, 2019;Meschitti, Smith, 2017). Multiple studies have shown that same-sex mentors can target professional development disparities for women early in their career and can be especially influential when students are determining their future career choice (Faucett et al, 2017;Gaetke-Udager et al, 2018;Lautenberger et al, 2019;Lewis et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Other research on female physicians and female entrepreneurs suggests women's more limited engagement in networking may be due to a lack of aspiration for organization leadership, lack of time, or a focus on seeking advice from within a smaller social circle (Chae, 2018;Mariam Malende, 2017). Regardless of the specific reasons, promoting same-sex mentorship is important as female students and trainees traditionally lack academic and professional mentors (Association of American Medical Colleges, 2017; Butkus et al, 2018;Colón-Emeric, Bowlby, and Svetkey, 2012;Burk-Rafel, Santen, and Purkiss, 2017;DeFilippis et al, 2016;Faucett et al, 2017;Gaetke-Udager et al, 2018;Lautenberger et al, 2019;Meschitti, Smith, 2017). Multiple studies have shown that same-sex mentors can target professional development disparities for women early in their career and can be especially influential when students are determining their future career choice (Faucett et al, 2017;Gaetke-Udager et al, 2018;Lautenberger et al, 2019;Lewis et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the specific reasons, promoting same-sex mentorship is important as female students and trainees traditionally lack academic and professional mentors (Association of American Medical Colleges, 2017; Butkus et al, 2018;Colón-Emeric, Bowlby, and Svetkey, 2012;Burk-Rafel, Santen, and Purkiss, 2017;DeFilippis et al, 2016;Faucett et al, 2017;Gaetke-Udager et al, 2018;Lautenberger et al, 2019;Meschitti, Smith, 2017). Multiple studies have shown that same-sex mentors can target professional development disparities for women early in their career and can be especially influential when students are determining their future career choice (Faucett et al, 2017;Gaetke-Udager et al, 2018;Lautenberger et al, 2019;Lewis et al, 2018). Women in medicine mentorship groups therefore may have a consequential role in addressing feelings of imposter syndrome, highlighting the importance of mentoring in building professional networks, and providing opportunities for women-focused networking (Faucett et al, 2017;Gaetke-Udager et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations